Characterization and bacterial toxicity of lanthanum oxide bulk and nanoparticles - Balusamy, Brabu; Kandhasamy, Yamuna Gowri; Senthamizhan, Anitha; Chandrasekaran, Gopalakrishnan; Subramanian, Murugan Siva; Kumaravel, Tirukalikundram S (Journal of rare earths, 2012)
This study evaluated the bacterial toxicity of lanthanum oxide micron and nano sized particles using shake flask method against gram-positive （Staphylococcus aureus） and gram-negative （Escherichia coli, Pseudomonas aeruginosa） bacteria. Particle size, morphology and chemical composition were determined using scanning electron microscopy （SEM） and energy dispersive X-ray spectroscopy （EDS）. Results indicated that lanthanum oxide nanoparticles showed antimicrobial activity against Staphylococcus aureus, but not against Escherichia coli and Pseudomonas aeruginosa. It was speculated that lanthanum oxide produced this effect by interacting with the gram-positive bacterial cell wall. Furthermore, lanthanum oxide bulk particles were fotmd to enhance the pyocyanin pigment production in Pseudomonas aeruginosa.